Investigating communication : (Prentice Hall, 1991)
This book provides a comprehensive, balanced introduction to communication research methods, and shows how communication research is conducted from start to finish, with the book's organization modeled after a traditional research study. By making the material accessible rather than impossible to learn, readers become excited about studying research methods